Hubungan Antara Stres Dengan Kualitas Tidur Pada Mahasiswa Yang Sedang Menyusun Skripsi Di Universitas “X” - Gina, Fathana; Putra, Alvin Rahma; Fahrudin, Adi (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is motivated by various sleep problems experienced by each individual, in this case, final year students who are preparing their thesis. Students are required to complete their thesis in order to obtain a bachelor's degree, but during the drafting process there are many obstacles which in the end make students difficult in the drafting process, so that it can have an impact on individual cognition which in this case is stress on students so that it affects sleep activities at night . The purpose of this study was to find out whether there is a relationship between stress and sleep quality in students who are preparing their thesis at “X” University. The method used is correlational quantitative. The subjects in this study were students who were compiling their thesis at "X" University, with data collection techniques using the Quota Sampling Technique with a total of 175 students using the Arikunto formula from a population of 1,746 students. Using Pearson Product Moment correlational analysis, it is known that there is a negative and significant relationship, which means that there is a negative relationship between stress and sleep quality in students who are preparing their thesis.